Can Big Data Achieve Environmental Justice? - Sunyowati, Dina; Indriani, Masitoh; Firdhausy, Annisa; Romadhona, Mochamad Kevin (Indonesian Journal of International Law, 2022)
Big data and analytical tools are being used by agricultural startup companies to develop their application performance. Generally, big data is a term that describes a large volume of structured and unstructured data. A few goals of its utilization include promoting environmental justice, improving energy efficiency, as well as tracking climate change by introducing ‘smart farms’. However, the utilization is accompanied by some flaws, such as legal regulatory issues involving the gap between applied technology and global government policies. There is also increased development of agricultural applications in Indonesia, which led to the initiation of a digitization program for plantation and livestock through the Go Online Farmers application. The roles of big data are very crucial in providing valuable information to farmers. Therefore, combining the observation of an agriculture-based application’s performance with a statutory approach, this research provided some examples of the utilization of big data by agriculture startup companies to achieve their environmental and sustainability goals. These include illustrating the initiative behind the use and the management of the associated policies and legal challenges in the country. Eventually, this research attempted to explain the contribution of big data in promoting environmental justice from a legal perspective.